Обзор и сравнение характеристик методов зондирования ионосферы сигналами с разными видами манипуляций - Бескровцев, Ф. Ю. (НТУ "ХПИ", 2003)
In article different views of signals, their limitation and advantages surveyed in examination of an ionosphere, and an opportunity of their application in the equipment of a radar incoherent dispersions. Some features of operation of the radio transmitter cicumscribed at application signals with différent views of manipulations equipments of a radar dependent on the circuit solution
Keywords: метод некогерентного рассеяния; зондирующий сигнал; радар; радиопередающие устройства; корреляционная обработка сигнала